Mendelian randomization based on genome-wide association studies and expression quantitative trait loci, predicting gene targets for the complexity of osteoarthritis as well as the clinical prognosis of the condition - Yan, Yiqun; He, Junyan; Xu, Zelin; Wang, Chen; Hu, Zhongyao; Zhang, Chun; Cheng, Wendan (Frontiers in Medicine, 2024)
Background: Osteoarthritis (OA) entails a prevalent chronic ailment, marked by the widespread involvement of entire joints. Prolonged low-grade synovial inflammation serves as the key instigator for a cascade of pathological alterations in the joints.The study seeks to explore potential therapeutic targets for OA and investigate the associated mechanistic pathways.Methods: Summary-level data for OA were downloaded from the GWAS database, eQTL data were acquired from the eQTLGen Consortium, and synovial chip data for OA were obtained from the GEO database. Following the integration of data and subsequent Mendelian Randomization analysis, Differential analysis, and WGCNA analysis, core genes that exhibit a significant causal relationship with OA traits were pinpointed. Subsequently, by employing three machine learning algorithms, additional identification of gene targets for the complexity of OA was achieved. Additionally, corresponding ROC curves and Nomogram models were established for the assessment of clinical prognosis in patients. Finally, Western blotting analysis and ELISA methodology were employed for the initial validation of marker genes and their linked pathways.Results: Twenty-two core genes with a significant causal relationship to OA traits were obtained. Through the application of distinct machine learning algorithms, MAT2A and RBM6 emerged as diagnostic marker genes. ROC curves and Nomogram models were utilized for evaluating both the effectiveness of the two identified marker genes associated with OA in diagnosis and treatment. MAT2A governs the synthesis of SAM within synovial cells, thereby thwarting synovial fibrosis induced by the TGF-β1-activated Smad3/4 signaling pathway.The first evidence that MAT2A and RBM6 serve as robust diagnostic and predictive indicators for OA is presented in this study. MAT2A, through its involvement in regulating the synthesis of SAM, inhibits the activation of the TGF-β1-induced Smad3/4 signaling pathway, thereby effectively averting the possibility of synovial fibrosis. Concurrently, the development of a prognostic risk model facilitates early OA diagnosis, functional recovery evaluation, and offers direction for further therapy.